Immunohistochemical-Based Detection of Human Cytomegalovirus in Brain Tissues from a Group of Iraqi Patients with Glioblastoma Multiforme and WHO Grade II Astrocytoma - Taha , Tamara Amer; Al-Shalchy, Ali; Bahaaldeen, Maysaa Awadh; Mohammed Ali, Saad Hasan; Al-Alwany, Shakir H. Mohammed; Al-Hijazi, Athraa Y.; Qassid, Omar Layth; Alkurtas, Mohammed (AL-Kindy College Medical Journal, 2025)
Background: Human Cytomegalovirus (HCMV) nucleic acids and proteins are frequently detected in brain tumors, especially high-grade gliomas in adults and children. Despite conflicting data, further investigation into HCMV’s role in gliomas is warranted. Objective: This study aimed to determine the frequency of HCMV proteins in tissues from patients at the Specialized Surgeries Hospital in Baghdad diagnosed with glioblastoma multiforme (GBM) and grade 2 astrocytoma. Subjects and Methods: Ninety-three (93) tissue samples were collected from patients aged 8-75 years: 46 samples from GBM surgeries and 27 from astrocytoma surgeries. An additional 20 samples collected from non-tumor neurosurgical patients such as (Eosinophilic granuloma and reactive gliosis) aged 21-71 years were included as a control group. Immunohistochemistry (IHC) was used to detect immediate early and early HCMV proteins. Results: Of the 73 glioma tissues, 38 (52.1%) showed positive IHC signals for HCMV. In GBM tissues, 28 out of 46 (59.9%) were positive, while in astrocytoma tissues, 10 out of 27 (38.4%) were positive. Only 1 out of 20 control tissues (5%) showed HCMV positivity. Within the GBM group, low, moderate, and high IHC scores were observed in 57.1%, 28.6%, and 14.3% of cases, respectively. In the astrocytoma group, scores were low in 60%, moderate in 30%, and high in 10%. Significant statistical differences were noted when comparing GBM and astrocytoma to the control group and comparing GBM to astrocytoma Conclusions: The study revealed a high prevalence of HCMV in glioma samples, supporting its potential role in glioma development, particularly in GBM pathogenesis and possibly carcinogenesis.